PERANCANGAN RANGKAIAN PENGATUR LAMPU LALU LINTAS PADA BERBAGAI PERSIMPANGAN JALAN - Rahardjo T.S., Kuat (Jurnal Teknik Elektro, 2006)
Much method to create a traffic light controller circuit, only depend on the component usedto build the circuit. But choosing the component depend on facilities to bee added to makethe driver satisfy through the street cross. In this article discuss five type off componentusually used, with more and less in every type off component.Keyword: Trafic light, controller, time sequence.